Understanding the Handling of Drinking Water in local communities in Kenya - Lukas Könneke (Hochschule für angewandte Wissenschaften Hamburg, 2019)
Drinking water has a great impact on people´s health and life expectancy. Waterborne diseases due to unsafe drinking water handling are a major cause of deaths in developing countries. To understand drinking water handling in a rural community in Kenya, several influencing factors need to be considered. For example, water sources, storage, treatment, consumption, sanitation and hygiene. This study was undertaken in a village called Mweiga near Nyeri Town in Central Kenya in order to understand the drinking water practices of a rural community. Method: The field research was conducted with an observation of the drinking water handling (storage and consumption) on household level. The observation was embedded in a face-to-face interview. Besides the socioeconomic background of the household, the interview investigated the health awareness on waterborne diseases and the occurrence of diarrhoea, cholera, typhoid hepatitis and polio as well as the knowledge about household water treatment. It also explored the sanitary and hygienic conditions of the households. Furthermore, field notes and photographs were taken to complement the findings. Results: Serious health concerns related to drinking water were recorded in the field research. Especially the number of people drinking untreated water frequently, despite knowing a method of household water treatment was alarming. The observation showed, that the hygienic behaviour of water consumption and storage was insufficient. Additionally, the sanitary conditions were likely to cause waterborne diseases. Conclusion: The study´s results have illustrated the high need of further health education regarding drinking water handling in Mweiga. Furthermore, there is a high necessity of household water treatment alternatives to water boiling. For rural areas in Kenya, community-based initiatives with empowered community members are needed to prevent diseases and deaths caused by unsafe drinking water.